The World in hemispheres with comparative views of the heights of the principal mountains and basins of the principal rivers on the globe. - Swanston, George H. (A. Fullarton & Co., 1852)
Map shows drainage of major rivers and relative heights of mountains throughout the Earth. Mountain heights are given in English feet. Insets: "Basins of the Amazon and Tocantins," "Basin of the La Plata," "Gt. Lakes & St. Lawrence," "Basin of the Mississippi & Missouri," "Basins of the Rhine, Danube & Dnieper," "Basins of the Volga & Ural," "Basins of the Indus," "Basins of the Ganges, Irawady," and "Basins of the Yenesei." Scale not given.